Reuse of tyre steel fibres as concrete reinforcement - Pilakoutas, Kypros; Neocleous, Costas; Tlemat, H. (My University, 2004)
To attain economically viable and environmentally friendly tyre recycling, it is necessary to develop new applications and products, which will use tyre by-products (especially the steel cord) as raw materials. The authors demonstrate that the steel fibres recovered from used tyres can be used to reinforce concrete elements. This application has a great potential, as it is estimated that more than 500000 t of high-quality steel fibres could be recovered annually from used tyres in the EU alone. This paper presents the work carried out as part of various ongoing projects on the use of steel fibres in concrete construction. The first part of the paper deals with waste management issues, the methods used to recover steel fibres from tyres, and existing applications of used tyres. The second part presents the mechanical behaviour of concrete elements reinforced with these steel fibres and discusses the relevant design and economic issues. It is concluded that the use of these steel fibres in concrete construction will benefit not only the construction industry, but also the producers and recyclers of used tyres.
Keywords: Concrete technology; Recycling of materials; Waste management & disposal